EKSPLORASI KONDISI PTSD SISWA SLTP DAN IMPLIKASINYA TERHADAP PELAYANAN KONSELING - Ardimen, Ardimen (Al-Qalb : Jurnal Psikologi Islam, 2016)
This study aims to explore the conditions PTSD junior high school students in the district of Tanah Datar. Exploration approach is done to identify the level / level and intensity of PTSD experienced by students that will be used for program development counseling services for junior high school. The data collection is done in junior high school students in Tanah Datar who experience PTSD and drawn at random. The results showed that a general overview of PTSD junior high school students in Tanah Datar cumulatively is the rate / level of PTSD experienced by students in middle category as much as 6%, lower as much as 9.6%, and is very low as much as 84.3%. Furthermore, no student who experienced PTSD at high and very high categories. However, as a specific for each condition and events that never experienced by students, there is still a small portion of students who experience PTSD at high and very high categories. To facilitate the development of students optimally formulated counseling services program includes four service components namely; basic services, responsive service, individual planning services, and support services system.